Planet friendly home-grown school feeding: Annexes - Borelli, Teresa; Nekesa, Tabitha; Mbelenga, Emiliana; Jumbale, Mwarome; Morimoto, Yasuyuki; Bellanca, Raffaella; Jordan, Irmgard (2024)
This document is related to the evaluation tool presented in the report on “Planet Friendly Home-Grown School Feeding – What does it mean?” published in July 2024. The tool includes 21 indicators and several agricultural, food processing, transport and storage practices associated with school feeding programs. The aim is to provide detailed information on why the practices presented in the tool have been categorized as planet hostile or planet friendly.